Comparison Between Repositioning Reduction Forceps and Intermaxillary Fixation with Eyelets in Anterior Mandibular Fracture Management: Repositioning Reduction Forceps and Intermaxillary Fixation - Zarmeena, .; Jamal, Muhammad Uzair; Rauf Shah, Syed Abdul; Parkash, Oam; Channar, Kashif Ali; Punjabi, Suneel Kumar (Pakistan Journal of Health Sciences, 2023)
Road traffic mishaps, lack of organized health-care facilities, and inadequate referral and transportation, particularly in rural regions, are boosting anterior mandibular fracture incidence. Objective: To compare the outcome of repositioning reduction forceps and Intermaxillary fixation (IMF) with eyelets in the anterior mandibular fracture management. Methods: Seventy consecutively sampled patients with isolated mandibular fractures were divided into two groups. IMF with eyelets was utilized to reduce mandibular fractures in group A and repositioning reduction forceps was used in group B. After mini plating, IMF was removed. Two observers assessed postoperative bony alignment, occlusion, lingual flaring and nonunion based on radiographs and findings. Results: Group A included 24 (68.6%) and 29 (82.9%) male patients, whereas group B had 11 (31.4%) and 6 (17.1%) female patients with mean ages of 27.9 ± 6.9 and 27.8 ± 8.9 years. In postoperative assessment, bony segments alignment (reduction) day-21 was present in all patients, lingual flaring at day-21, 1 (2.9%) and 2 (5.7%) patients, gap in fracture segments at day 21 was > 5mm in all subjects, malocclusion at day 21, 0 (0.0%) and 1 (2.9%) in group A and B respectively. Day 21 showed no non-union in any group. Conclusions: IMF with eyelets and repositioning reduction forceps improves bone segment alignment (reduction), lingual flare, fracture gap, and malocclusion.